Television history: archives, excavation and the future. A discussion. Issue 1 (March 2016) - Smart, Billy; Wrigley, Amanda
This article considers possible futures for television (TV) studies, imagining how the discipline might evolve more productively over the next 10 years and what practical steps are necessary to move towards those outcomes. Conducted as a round-table discussion between leading figures in television history and archives, the debate focuses on the critical issue of archives, considering and responding to questions of access/inaccessibility, texts/contexts, commercial/symbolic value, impact and relevance. These questions reflect recurrent concerns when selecting case studies for historical TV research projects: how difficult is it to access the material (when it survives)? What obstacles might be faced (copyright, costs, etc.) when disseminating findings to a wider public? The relationship between the roles of 'researcher' and 'archivist' appears closer and more mutually supportive in TV studies than in other academic disciplines, with many people in practice straddling the traditional divide between the two roles, combining specialisms that serve to further scholarship and learning as well as the preservation of, and broad public engagements with, collections. The Research Excellence Framework's imperative for academic researchers to achieve 'impact' in broader society encourages active and creative collaboration with those based in public organizations, such as the British Film Institute (BFI), who have a remit to reach a wider public. The discussion identifies various problems and successes experienced in collaboration between the academic, public and commercial sectors in the course of recent and ongoing research projects in TV studies.